THE POETIC REPRESENTATION OF CHARACTERS’ INNER WORLDS IN “VIRTUAL LIGHT” (KONFERENSIYA, 2025)
This article explores how William Gibson’s Virtual Light showswhat is going on inside its characters, paying special attention to how monologue,dialogue, landscape, and portrait are used through comparisons with modernist,realist and dystopian novels